2019
DOI: 10.1016/j.cemconres.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A modified accelerated chloride migration tests for UHPC and UHPFRC with PVA and steel fibers

Abstract: Accelerated migration tests which are commonly used to measure chloride diffusion in ordinary cement-based materials cannot be directly applied to composite with very low permeability, such as Ultra High-Performance Fiber Reinforced concretes (UHPFRC). In order to assess the UHPFRC enhancement on the structural durability, there is a critical need to accurately assess the permeability level of the material to chloride ions. The objective of this work is to adapt an existing set-up of accelerated chloride migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 11 publications
(6 reference statements)
0
4
1
Order By: Relevance
“…In our study, the diffusion coefficients of 0.41 × 10 −14 m 2 /s and 0.08 × 10 −14 m 2 /s for 7 and 28 days were significantly lower than in the study by Teng [57]. They were also significantly lower than those of UHPC [54,58]. It appears the fine RUFA and silica fume particles increased particle packing effects within the specimens.…”
Section: Permeabilitycontrasting
confidence: 76%
See 1 more Smart Citation
“…In our study, the diffusion coefficients of 0.41 × 10 −14 m 2 /s and 0.08 × 10 −14 m 2 /s for 7 and 28 days were significantly lower than in the study by Teng [57]. They were also significantly lower than those of UHPC [54,58]. It appears the fine RUFA and silica fume particles increased particle packing effects within the specimens.…”
Section: Permeabilitycontrasting
confidence: 76%
“…The finer particles consumed a larger quantity of calcium hydroxide to produce C-S-H colloids during hydration, which helped to improve the compactness of the mortar and reduce permeability. We found that UHPG containing ultra-fine particles far outperformed plain UHPC specimens containing fibers [5,54,58,59]. The fibers enhanced the tensile strength and toughness of UHPC but weakened the interfacial transition zone and increased the chloride diffusion coefficient.…”
Section: Permeabilitymentioning
confidence: 89%
“…When chloride ions diffuse into the bridge deck, they cause corrosion and expansion of steel bars, which lead to cracking and affect the safety of the structure. In order to analyze the chloride permeability of SMC, a rapid chloride permeability test was carried out according to the procedure described in ASTM C1202 [ 36 , 37 , 38 , 39 ]. The test device is shown in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
“…The low diffusion coefficient for chloride ions is attained when using hybrid combinations of SFs and PPFs. It has been observed that the development of corrosion around SFs and the presence of discontinuities between the fibers and OPC can accelerate the ingress of chloride ions into the sample [ 137 ]. Employing PPFs serves as an effective method to mitigate this concern in ultra-high-performance geopolymer concrete.…”
Section: Durability Characteristics Of Uhpgpcmentioning
confidence: 99%